2004
DOI: 10.1093/aje/kwh134
|View full text |Cite
|
Sign up to set email alerts
|

Application of a New Statistical Method to Derive Dietary Patterns in Nutritional Epidemiology

Abstract: Because foods are consumed in combination, it is difficult in observational studies to separate the effects of single foods on the development of diseases. A possible way to examine the combined effect of food intakes is to derive dietary patterns by using appropriate statistical methods. The objective of this study was to apply a new statistical method, reduced rank regression (RRR), that is more flexible and powerful than the classic principal component analysis. RRR can be used efficiently in nutritional ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
687
0
19

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 562 publications
(718 citation statements)
references
References 48 publications
12
687
0
19
Order By: Relevance
“…Similar comparison studies also showed that in general PCA-derived patterns explain more variance of the food groups but explain less of the variance in response variables (Hoffmann et al 2005;Hoffmann et al 2004). Our first RRR pattern explained 40.5% of the response variable variation, which is in line with results from other studies (Biesbroek et al 2015;Hoffmann et al 2005;Hoffmann et al 2004), but clearly leaves a proportion of the variance unexplained. Other factors, such as socioeconomic status, age, or gender might also impact GHG emissions of the diet and dietary quality.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Similar comparison studies also showed that in general PCA-derived patterns explain more variance of the food groups but explain less of the variance in response variables (Hoffmann et al 2005;Hoffmann et al 2004). Our first RRR pattern explained 40.5% of the response variable variation, which is in line with results from other studies (Biesbroek et al 2015;Hoffmann et al 2005;Hoffmann et al 2004), but clearly leaves a proportion of the variance unexplained. Other factors, such as socioeconomic status, age, or gender might also impact GHG emissions of the diet and dietary quality.…”
Section: Discussionmentioning
confidence: 53%
“…Examples of these models are principle component analysis (PCA) or cluster analysis (CA) (Hearty and Gibney 2009;Newby and Tucker 2004;Stricker et al 2013). Both a priori and a posteriori techniques have been combined in a relatively new method: reduced rank regression (RRR) (Hoffmann et al 2004). When combining dietary information with known biomarkers for a disease, RRR was able to derive dietary patterns that showed stronger associations with a particular disease than PCA-based patterns (Hoffmann et al 2004;Nettleton et al 2007;Schulze and Hoffmann 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of both methods has gained increasing popularity in the past decade and the literature has burgeoned in recent years 7,8,9 . The main technique used in the "a posteriori" approach is the analysis of principal components and subsequent factor analysis 10 .…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the effect of overall diet on chronic diseases, other studies have identified dietary patterns using factor analysis and/or cluster analysis or a more recent method called reduced rank regression (Hu, 2002;Hoffmann et al, 2004;Kant, 2004;Schulze and Hoffmann, 2006).…”
Section: Introductionmentioning
confidence: 99%